2014
DOI: 10.1111/ceo.12386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the chorioretinal thickness changes in Alzheimer's disease using spectral‐domain optical coherence tomography

Abstract: Patients with AD had chorioretinal structural alterations. Retinal structural alterations were seen only in the inner layers. The reduction in mGCC thickness parameters were related to the severity of cognitive impairment in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 37 publications
13
122
1
6
Order By: Relevance
“…Figure 3 depicts these changes in choroidal thickness. These findings have been corroborated by further studies [62,63]. One study also included patients with MCI, and observed reduced CT in this group, although no statistically significant differences between the MCI and AD patient groups were found [63].…”
Section: Pathological Changes In the Retina And Optic Nervesupporting
confidence: 64%
See 1 more Smart Citation
“…Figure 3 depicts these changes in choroidal thickness. These findings have been corroborated by further studies [62,63]. One study also included patients with MCI, and observed reduced CT in this group, although no statistically significant differences between the MCI and AD patient groups were found [63].…”
Section: Pathological Changes In the Retina And Optic Nervesupporting
confidence: 64%
“…More recent OCT studies have reported also macular changes in the ganglion cell complex (GCC), comprising the ganglion cell layer (GCL) and inner plexiform layer (IPL). Also, choroidal thickness [60] has been shown to be reduced in patients with AD, as measured by EDI-OCT Spectralis Heidelberg [61][62][63].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…In some studies performed on dementia-group diseases causing cognitive impairment, a significant correlation was found between the MMSE score and RNFL thickness (30,31) . In addition, in a study by Bayhan et al, a significant correlation was (32) found between the MMSE score and the mean GC-IPL thickness. Conversely, in another study, no correlation was found between the MMSE score and RNFL thickness (33) .…”
Section: Discussionmentioning
confidence: 86%
“…Historically, these visual and circadian rhythm disturbances were attributed to pathology in the brain yet are now being revisited and explored as a potential direct outcome of ocular pathologies. Among ocular tissues, studies have shown that the retina is massively impacted by AD [466, 472, 474479, 482, 484, 486, 487, 490507]. The retina of MCI subjects and AD patients displays a host of abnormalities including nerve fiber layer (NFL) thinning, optic nerve and retinal ganglion cell (RGC) degeneration, macular volume changes, retinal angiopathy involving reduced blood flow and vascular structural alterations, astrogliosis, and abnormal electroretinogram patterns [472].…”
Section: Contribution and Role Of Retinal Imagingmentioning
confidence: 99%